2019
DOI: 10.1002/jsfa.9508
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and meat quality characteristics of seven primal cuts from 9‐month‐old female veal calves: a preliminary study

Abstract: BACKGROUND Beef is a highly nutritious and valuable food. In order to complete its nutritional information, this study determined the chemical and physicochemical parameters and fatty acid, amino acid and mineral contents in seven primal cuts from veal carcasses (shoulder clod (SC), inside round (IR), eye of round (ER), bottom round (BR), heel of round (HR), knuckle (KK) and tenderloin (TL)). RESULTS The intramuscular fat content was higher and the cholesterol content was lower in TL than in the other cuts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…Content of saturated fatty acids did not differ, but content of monounsaturated and polyunsaturated fatty acids differ significantly (P<0.05) between some LBW groups (Table 3). Contrariwise to Blanco et al (2010) and Gálvez et al (2018), we found higher content of monounsaturated fatty acids in veal loin. Content of palmitic acid, which is known to have a cholesterolemic effect was significantly higher (P<0.001) in the lightest group of calves.…”
Section: Resultssupporting
confidence: 88%
“…Content of saturated fatty acids did not differ, but content of monounsaturated and polyunsaturated fatty acids differ significantly (P<0.05) between some LBW groups (Table 3). Contrariwise to Blanco et al (2010) and Gálvez et al (2018), we found higher content of monounsaturated fatty acids in veal loin. Content of palmitic acid, which is known to have a cholesterolemic effect was significantly higher (P<0.001) in the lightest group of calves.…”
Section: Resultssupporting
confidence: 88%
“…The pivotal issue for genomic selection is to establish the reference population and candidate population for better selection of the paternal and maternal candidates [57]. To improve the meat quality of beef, increasing the marbling (or intramuscular fat) content is an efficient and necessary approach [58]. Understanding the molecular basis of the miR-23a~27a~24-2 cluster in adipogenesis can provide new insights for selecting candidates with more intramuscular fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Before color measurements, muscles were freshly cut and allowed to bloom directly in contact with air for 20 min. Colorimetric parameters (L*, a*, and b*) were measured as described by Gálvez et al [ 21 ], using a Minolta CR-300 colorimeter (Light Source D65, Minolta Camera Co., Osaka, Japan). Measurements were collected from a 0° viewing angle with A-pulsed xenon arc lamp, with a reading surface of 8-mm diameter.…”
Section: Methodsmentioning
confidence: 99%